Better post-operative prediction and management of chronic pain in adults after total knee replacement: the multidisciplinary STAR research programme including RCT - Gooberman-Hill, R; Wylde, V; Bertram, W; Moore, AJ; Pinedo Villanueva, R; Sanderson, E; Dennis, J; Harris, S; Judge, A; Noble, S; Beswick, AD; Burston, A; et al. (NIHR Journals Library, 2023)
Background: The treatment of osteoarthritis with knee replacement aims to reduce pain and disability. However, some people experience chronic pain. Objectives: To improve outcomes for people with chronic pain after knee replacement by identifying post-surgical predictors and effective interventions, characterising patient pathways and resource use, developing and evaluating a new care pathway, and exploring non-use of services. Design: The programme comprised systematic reviews, national database analyses, a cohort study, intervention development, a randomised controlled trial, health economic analyses, qualitative studies and stakeholder engagement. Extensive and meaningful patient and public involvement underpinned all studies. Setting: NHS, secondary care, primary care. Participants: People with, or at risk of, chronic pain after knee replacement and health-care professionals involved in the care of people with pain. Interventions: A care pathway for the management of people with pain at 3 months after knee replacement. Main outcome measures: Patient-reported outcomes and cost-effectiveness over 12 months. Data sources: Literature databases, the National Joint Registry, Hospital Episode Statistics, patient- reported outcomes, the Clinical Practice Research Datalink, the Clinical Outcomes in Arthroplasty Study, the Support and Treatment After joint Replacement randomised trial, interviews with 90 patients and 14 health-care professionals, and stakeholder events. Review methods: Systematic reviews of cohort studies or randomised trials, using meta-analysis or narrative synthesis. Results: In the Clinical Outcomes in Arthroplasty Study cohort, 14% of people experienced chronic pain 1 year after knee replacement. By 5 years, 65% reported no pain, 31% fluctuated and 4% remained in chronic pain. People with chronic pain had a worse quality of life, higher primary care costs, and more frequent analgesia prescriptions, particularly for opioids, than those not in chronic pain. People with chronic pain after knee replacement who made little or no use of services often felt nothing more could be done, or that further treatments may have no benefit or cause harm. People described a feeling of disconnection from their replaced knee. Analysis of UK databases identified risk factors for chronic pain after knee replacement. Pre- operative predictors were mild knee pain, smoking, deprivation, body mass index between 35 and 40 kg/m2 and knee arthroscopy. Peri- and post-operative predictors were mechanical complications, infection, readmission, revision, extended hospital stay, manipulation under anaesthetic and use of opioids or antidepressants. In systematic reviews, pre-operative exercise and education showed no benefit in relation to chronic pain. Peri-operative interventions that merit further research were identified. Common peri- operative treatments were not associated with chronic pain. There was no strong evidence favouring specific post-operative physiotherapy content. We evaluated the Support and Treatment After joint Replacement care pathway in a multicentre randomised controlled trial. We randomised 363 people with pain at 3 months after knee replacement from eight NHS Trusts in England and Wales. At 12 months’ follow-up, the intervention group had lower mean pain severity (adjusted difference –0.65, 95% confidence interval –1.17 to -0.13; p = 0.014) and pain interference (adjusted difference –0.68, 95% confidence interval –1.29 to -0.08; p = 0.026), as measured on the Brief Pain Inventory subscales (scale 0–10). People receiving the Support and Treatment After joint Replacement pathway had lower NHS and Personal Social Services costs (–£724, 95% confidence interval –£150 to £51) and higher quality-adjusted life-years (0.03, 95% confidence interval –0.008 to 0.06) than those with usual care. The Support and Treatment After joint Replacement pathway was cost-effective with an incremental net monetary benefit at the £20,000 per quality-adjusted life-year threshold of £1256 (95% confidence interval £164 to £2348), indicating a 98.79% probability that the intervention is the cost-effective option. Participants found the Support and Treatment After joint Replacement pathway acceptable, with opportunities to receive information and discuss concerns while ensuring further treatment and support. In systematic reviews considering treatments for chronic pain after surgery we identified some unifactorial interventions that merit further research after knee replacement. Health-care professionals delivering and implementing the Support and Treatment After joint Replacement pathway valued its focus on neuropathic pain and psychosocial issues, enhanced patient care, formalised referrals, and improved pain management. Stakeholders supported pathway implementation. Limitations: Database analyses were limited to factors recorded in data sets. Pain was only measured 6 months after surgery. However, analyses including large numbers of centres and patients should be generalisable across the NHS. In many studies found in systematic reviews, long-term pain was not a key outcome. Conclusions: The Support and Treatment After joint Replacement pathway is a clinically effective and cost-effective, acceptable intervention for the management of chronic pain after knee replacement. Unifactorial interventions merit further study before inclusion in patient care. People with pain should be empowered to seek health care, with the support of health-care professionals. Future work: Future work should include research relating to the implementation of the Support and Treatment After joint Replacement pathway into the NHS, an assessment of its long-term clinical effectiveness and cost-effectiveness and wider application, and an evaluation of new interventions for incorporation in the pathway. It will also be important to design and conduct research to improve communication between patients and health-care professionals before surgery; explore whether or not education and support can enable earlier recognition of chronic pain; consider research that may identify how to support people’s feelings of disconnectedness from their new knee; and design and evaluate a pre-surgical intervention based on risk factors. Study registration: All systematic reviews were registered on PROSPERO (CRD42015015957, CRD42016041374 and CRD42017041382). The Support and Treatment After joint Replacement randomised trial was registered as ISRCTN92545361. Funding: This project was funded by the National Institute for Health and Care Research (NIHR) Programme Grants for Applied Research programme and will be published in full in Programme Grants for Applied Research; Vol. 11, No. 3. See the NIHR Journals Library website for further project information.